Niching as a Macrostructural Procedure - Gouws, Rufus H. (Lexikos, 2002)
Abstract: Niching is a macrostructural procedure of textual condensation which results in different dictionary articles being clustered into one textblock as subarticles headed by sublemmata. This article offers an identification and critical discussion of different types of niching. Examples from dictionaries are used to examine problems which dictionary users experience as a result of the application of niching. The emphasis is on problems regarding the search route of users via the outer access structure of dictionaries. A distinction is made between single niching and multiple niching. Different aspects of multiple niching receive attention, e.g. the use of remote and exclusively remote multiple niching. The focus is also on an increased degree of textual condensation resulting from these procedures as well as problems in the domain of the access structure. Attention is drawn to the influence of the inclusion of homonym pairs on the application of multiple niching. Problems arising from an inconsistent application of multiple niching are identified and solutions are suggested for these problems in order to enhance the quality of the lexicographic practice. It is shown that a user-driven dictionary would rather opt for the application of procedures of single niching and first level nesting instead of multiple niching. Keywords: EXCLUSIVELY REMOTE MULTIPLE NICHING, FIRST LEVEL NESTING, HETEROGENEOUS NICHING, HOMOGENEOUS NICHING, HYBRID NICHING, MULTIPLE NICHING, NESTING, NICHING, PARTIAL ARTICLE STRETCH, REMOTE NICHING, SINGLE NICHING, TEXTUAL CONDENSATION Opsomming: Nisting as ’n makrostrukturele prosedure. Nisting is ’n makrostrukturele teksverdigtingsprosedure waardeur woordeboekartikels in een teksblok as subartikels met sublemmata gegroepeer word. Hierdie artikel bevat ’n beskrywing en kritiese bespreking van verskillende tipes nisting. Aan die hand van woordeboekvoorbeelde word probleme wat gebruikers met die toepassing van verskillende nistingsmetodes kan h?, onder die loep geneem. Daar word veral gefokus op probleme wat nisting kan skep met betrekking tot die soekroete van gebruikers op die eksterne toegangstruktuur van woordeboeke. ’n Onderskeid word gemaak tussen enkelnisting en veelvuldige nisting. Verskillende aspekte van veelvuldige nisting word ondersoek, onder meer die gebruik van verwyderde en eksklusief verwyderde veelvuldige nisting. Die verhoogde graad van teksverdigting wat daardeur teweeggebring word asook die toegangstruktuurprobleme word bespreek. Aandag word ook gegee aan die invloed wat die opname van homoniempare op veelvuldige nisting het. Leemtes en inkonsekwenthede in die toepassing van veelvuldige nisting word bespreek en voorstelle word aan die hand gedoen ter verbetering van die huidige toepassing daarvan in die leksikografiepraktyk. Daar word aangedui dat ’n gebruikersgedrewe woordeboek eerder van veelvuldige nisting moet afstand doen ten gunste van prosedures van enkelnisting en eerstevlaknesting. Sleutelwoorde: EERSTEVLAKNESTING, EKSKLUSIEF VERWYDERDE NISTING, ENKELNISTING, GEDEELTELIKE ARTIKELREEKS, HETEROGENE NISTING, HIBRIDIESE NISTING, HOMOGENE NISTING, NESTING, NISTING, TEKSVERDIGTING, VEELVULDIGE NISTING, VERWYDERDE NISTING